SINTESIS SURFAKTAN ALKIL POLIGLIKOSIDA DARI GLUKOSA DAN DODEKANOL DENGAN KATALIS ASAM - Anastasia Wulan Pratidina Swasono, Putri Dei Elvarosa Sianturi, Zuhrina Masyithah (Universitas Sumatera Utara, 2012)
Alkyl polyglicoside (APG) is an enviromentally friendly product non-ionic surfactact and biodegradable product that can be obtained by reacting glucose and fatty alcohol. The purpose of this study was to know the manufacture of surfactant alkyl polyglicoside by using glucose and dodecanol, and also to know the effect of catalyst concentration and molar ratio glucose and dodecanol: 1:1; 1:2: 2:1 (mol/mol), catalyst consentration of hydrochloric acid: 0.3 M; 0,4 M; 0,5 M; 0,6 M at temperature 100 0C. The analysis in this research using FT-IR spectroscopy, analysis of surface tension (Critical Micelle Concentration) and HLB values ​​(Hidrophylic-Lipophylic Balance). The best catalyst concentration at synthesis of alkyl polyglicoside is 0.6 M, the largest surface tension (CMC) at ratio glucose and dodecanol 2:1 is 70.7945% and the highest HLB value is 7.31 in comparison of glucose and dodecanol 2:1.Keywords : surfactant, glucose, dodecanol, FT-IR spectroscopy, HLB